Party girl [videorecording (DVD)] - Birckmayer, Harry, 1963-; Posey, Parker, 1968-; De Sando, Anthony; Díaz, Guillermo, 1975-; Mitchell, Donna (Actress); Schreiber, Liev; Townsend, Omar; Von Scherler, Sasha (Columbia TriStar, 2003)
A 20-something club girl needs some steady income after the cops bust her for throwing an illegal rent party. She gets a job as a library clerk and discovers the wonders of the Dewey Decimal system.